PS02.226: PREDICTIVE FACTORS FOR EARLY RECOVERY OF ORAL INTAKE IN PATIENTS WHO UNDERWENT CURATIVE ESOPHAGECTOMY FOR ESOPHAGEAL CANCER. (14th September 2018) - Isobe, Yujiro; Kawakubo, Hirofumi; Amada, En; Mayanagi, Shuhei; Fukuda, Kazumasa; Nakamura, Rieko; Wada, Norihito; Suda, Koichi; Ando, Makiko; Ishikawa, Aiko; Muraoka, Kaori; Kitagawa, Yuko
Abstract: Background: Evaluating swallowing function by Videoendoscopic evaluation of swallowing (VE) and Videofluorography (VF) is vital in reintroducing oral diet to patients who underwent esophagectomy. However, performing VE and VF requires specific facility and experts. So, the aim of this study is to evaluate predictive factors for early recovery of oral intake. Methods: One-hundred and thirty-six patients who underwent minimally invasive esophagectomy for thoracic esophageal cancer with three-field-lymph node dissection were enrolled. Patients' characteristics, surgical and pathological factors, postoperative complications, duration from surgery to reintroducing oral intake, results of repetitive saliva swallowing test (RSST) and maximum phonation time (MPT) on seventh postoperative day (7POD) were analyzed. We classified patients that duration of reintroducing oral intake is shorter than 10 days into Normal-intake (N) group and patients that duration of oral intake is longer than 11 days into Delayed-intake (D) group. Results: The average age of all patients was 64 ± 9 years old and average hospital stay of them was 30 ± 15 days. Three-field-lymph node dissection was performed in 96% of the cases and all patients have been performed cervical esophagogastrostomy. N group had significantly many patients who completed neoadjuvant chemo(radio)therapy (neo-C(R)Tx)) compared to D group (74% vs. 51%, P = 0.01). Also, patients in N group had significantly low level of preoperative indocyanine green test (ICG test; determined by colorimetric method at 15 minutes after injection of indocyanine green solution) and maximum postoperative serum C-reactive protein level until 7POD (max-CRP) compared to D group ( P = 0.047, P = 0.001, respectively). Moreover, average time of MPT on 7POD was long in N group compared to D group ( P = 0.05). In multivariate analysis, completion of neo-C(R)Tx, ICG ≤ 9, max-CRP ≤ 14.5 mg/dL was independent predictive factor of early recovery of oral intake (OR: 2.6 P = 0.023, OR: 4.6 P = 0.003, OR: 1.7 P = 0.008, respectively). Conclusion: Preoperative good liver function, completion of neoadjuvant treatment and relatively low postoperative inflammation were considered to be predictive factors for early recovery of oral intake in patients who underwent curative esophagectomy for esophageal cancer. Disclosure: All authors have declared no conflicts of interest.